Decrease in Aβ42 predicts dopa-resistant gait progression in early Parkinson disease - Rochester, Lynn (Neurology, 2017)
OBJECTIVE: This prospective observational study investigates the role of CSF biomarkers in predicting progression of dopa-resistant gait impairments in Parkinson disease (PD) in the first 36 months from diagnosis. METHODS: Quantitative gait analysis was carried out longitudinally using an instrumented walkway (GAITRite) in 108 people with PD and 130 age-matched controls. A subgroup of 44 people with PD underwent lumbar puncture from which a battery of CSF biomarkers was measured: β-amyloid 1–42 and 1–40 (Aβ42 and Aβ40), total and phosphorylated tau protein (t-tau/p-tau(181)), and α-synuclein (αSyn). Linear mixed models examined the association between CSF and dopa-resistant gait characteristics (defined as substantial progression despite optimal medication). RESULTS: Low baseline CSF Aβ42, and to a lesser extend Aβ40, predicted decline in gait characteristics in the first 3 years following diagnosis, independently explaining up to 12% of progression of step time variability (single task) and step length variability (dual-task). Interestingly, these findings were independent of age and cognition. CONCLUSIONS: These findings implicate underlying amyloid pathology in neural networks involved in locomotor control. Results suggest that disturbed Aβ metabolism may be a biomarker for dopa-resistant gait impairments in early PD. Our findings raise interesting questions regarding therapeutic interventions such as compounds or molecules aimed at reducing amyloid burden to mitigate gait disturbance in early PD and potentially falls risk. Finally, progression of discrete gait characteristics suggests they may have potential as clinical biomarkers of pathology and disease progression.